(untitled) (Veterinária Notícias, 2023)
This study compared three methods for estimating forage mass and its morphological components in canopies of Urochloa brizantha cv. Marandu (marandu palisadegrass). Two experiments were carried out, the fi rst simulating deferment and the second, continuous stocking. In the fi rst experiment, three methods for estimating forage mass (square, row, and tiller methods) were evaluated in different canopies with three initial heights (15, 30, and 45 cm). In the second experiment, two methods for estimating forage mass (square and tiller methods) were evaluated in canopies with three average heights (15, 30, and 45 cm) in summer. The experiments were conducted in a completely randomized design, in a split-plot scheme, with four replications. The plots were canopy heights and the subplots, the forage mass estimation methods. In general, taller canopies have greater forage mass. The tiller method resulted in lower total forage and senescent forage masses than the other methods. The tiller method underestimates total forage and senescent forage masses. The square and line methods are suitable to estimate the pasture total and senescent forage masses.